Medical thoracoscopy/pleuroscopy : manual and atlas - Loddenkemper, Robert (Stuttgart ; New York : Thieme, 2011)
"In this atlas, the authors (European and American specialists) demonstrate the value of thoracoscopy and provide the details necessary for the novice by combining textbook and atlas formats. This book encompasses the history of thoracoscopy, as well as its technical characteristics and the morphological appearance of pathologic tissues, based on the authors' personal experiences and on the literature. The authors emphasize those technical areas where thoracoscopy differ from other types of endoscopy. Photographs are supplemented by case reports which illustrate the indications, techniques, and outcome of the procedure. The book is organized according to clinical criteria on which the physician can base his or her decision to perform thoracoscopy. Because of the variability of presentation, common diseases are shown in several manifestations, whereas more rare diseases are presented only when their thoracoscopic appearance is characteristic. This atlas also includes new developments in video-assisted thoracoscopic surgery (VATS). Camera optics (as opposed to video optics) have been used to produce high quality images"--Provided by publisher.
(Publisher-supplied data) Anatomy and physiopathology of the middle ear -- Anesthesia and surgical field -- Surgical materials -- Management of tympanic membrane abnormalities -- Management of ossicular abnormalities -- Management of cholesteatoma -- Dressing and postoperative care.
Includes bibliographical references (p. 156-170) and index.
Keywords: Thoracoscopy -- Handbooks, manuals, etc; Thoracoscopy -- Atlases; Thoracoscopy -- methods; Pleural Cavity -- surgery; Thoracoscopy -- Atlases